EMOTIONAL INTELLIGENCE AND STUDY HABITS ON LEARNING ACHIEVEMENT AT SENIOR HIGH SCHOOL - Chairani, Fani; Faslah, Roni; Wahono, Puji (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The purpose of this study was to examine the effect of Emotional Intelligence and Learning Habits on Learning Achievement at SMA Budhi Warman II Jakarta. Data collection in this study used secondary data from the school in the form of student grades and primary data using a questionnaire on the Google Form application with a proportionate stratified random sampling technique. The sample used in this study was 180 students from a total population of 327 students. This study used SPSS by calculating multiple regression analysis to test the data hypothesis. The results of this study indicate that Emotional Intelligence and Learning Habits have a positive and significant effect on Learning Achievement both partially and simultaneously. The contribution of this study is to provide an empirical understanding that emotional intelligence and learning habits significantly affect student learning achievement, so that it can be a basis for schools to design more effective student development strategies.